Sustainable Approaches to Synthesis SnO2/MWCNT Nanocomposite Using Eggplant Extract: Study Structural Optical and Morphological Properties: Pendekatan Berkelanjutan untuk Sintesis Nanokomposit SnO2/MWCNT Menggunakan Ekstrak Terong: Mempelajari Sifat Optik dan Morfologi Struktural - Kadhim , Oday Jawad; Thamer , Ahmed A. (Academia Open, 2025)
To develop eco-friendly methods in nanotechnology, an innovative approach to the fabrication of SnO₂/MWCNT nanocomposites using an easily used yet effective green method was achieved. This study shows a sustainable route to highly reducing chemical synthesis, using the natural reducing properties of the eggplant extract. Working successfully, the research was able to create a hybrid nanomaterial comprised of tin oxide (SnO₂) and multi walled carbon nanotubes (MWCNTs) using a simple co-precipitation technique. Combining SnO₂ and MWCNT resulted in a nanocomposite with an intriguing transformation from nanotubular to flower-like structures and uniform distribution of the particles. Detailed analysis showed a crystallite size of ~ 21.75 nm for pure SnO₂ up to 38.98 nm in the hybrid form and retained good uniformity ~ 45.84 nm. Most importantly, the integration of MWCNTs yielded an optimized bandgap reduction from 3.5 to 3.1 eV, improving the material’s light absorption ability. Such improvement opens up exciting applications in photocatalysis, gas sensing and energy storage devices. This eco friendly synthesis method is proven to be viable for creating green advanced nanomaterials, which not only provides proof of concept for green approach in creating advanced nanomaterials but allows for more sustainable practices in nanotechnology development while keeping the high performance standards needed for practical applications. Highlights: Eco-friendly SnO₂/MWCNT synthesis using eggplant extract Green nanotechnology: improved bandgap, structure, and uniformity Applications in photocatalysis, gas sensing, and energy storage Keywords: SnO2 NPs, SnO2/MWCNT, Eggplant Extract, green synthesis